Private education and socioeconomic school segregation in the Buenos Aires Province, Argentina - Krüger, Natalia (Ediciones UNL. Secretaría de Extensión de la UNL, 2022)
Socioeconomic school segregation is currently one of the most relevant manifestations of inequality experienced by different social groups within Latin American educational systems. Since the phenomenon has specific characteristics in each context, it is of interest to analyze it in sub–national settings, where its study is still scarce. Following a quantitative approach, this paper analyzes the problem in basic educationin the Buenos Aires Province, Argentina, with an emphasis on the distribution of students between the public and private sectors. To this end, census data from the national program of educational evaluation Aprender for the secondary level (November 2017) and the primary level (October 2018) areused. Indices of segregation are estimated and various indicators of the socioeconomic profile of the population attending each sector are compared. Findings indicate that there is a significant degree of segregation at both educational levels and that the participation of the private sector plays a substantial role.The distribution of students between and within both school networks is uneven, so that the probability of interacting at school with peers from other social groups is limited. The results invite us to replicate the study in other contexts; to ponder on the impact of the phenomenon on educational and social equity; and to continue investigating its causes and possible ways to overcome it.